Caregiver practice and quality of life among children with cerebral palsy - Eka Sulistiyawati; Abdul Wahab; Rosalia Kurniawati Harisaputra (Berita Kedokteran Masyarakat, 2026)
Purpose: This study explored how caregiver practices relate to the quality of life (QoL) of children with cerebral palsy (CP) in Surakarta, with particular attention to caregiver adherence to recommended care and to CP severity as determinants of QoL outcomes. Methods: A retrospective cohort design was employed involving 163 children with CP and their primary caregivers in Surakarta. Data were collected from medical and caregiver records to assess caregiver adherence to recommended care practices, severity of CP, and children’s QoL. Statistical analyses were conducted to determine the strength of associations between caregiver adherence, CP severity, and QoL outcomes. Results: High caregiver adherence was significantly associated with improved QoL in children with CP. Children whose caregivers showed high adherence were 2.75 times more likely to have better QoL than those with low adherence. Additionally, CP severity emerged as a strong predictor of QoL, with more severe cases associated with poorer QoL. Conclusion: The findings suggest that caregiver practices, particularly consistent adherence to recommended care plays an important role in supporting the quality of life of children with CP. At the same time, the clinical severity of CP remains a key influencing factor. Strengthening caregiver training, improving access to healthcare support, and promoting more holistic rehabilitation approaches may therefore improve long-term outcomes for children with CP.